The Awareness of Dental Check-Up and The Value of Aesthetic Restoration Amongst Undergraduates at the University of Ibadan, Southwest Nigeria (African Journal of Biomedical Research, 2020)
The aim of the study was to create the need for awareness of dental check-up; and to access the value for aesthetic dental restoration. A descriptive cross-sectional study was done with the use of self-administered questioners designed in a clear message expressed in English language including 20 questions were distributed to undergraduate age range 16-30 years in the University of Ibadan. A total of 417 students responded to the questionnaire of which 92.1% are aware about dental check-up, 46.8% have had pain and discomfort from tooth,19% have tooth fracture, 20% have tooth discolouration, 27%  have visited a dentist, 2.9% have a tooth coloured filling,7% are wearing removable denture .The result of this study shows an awareness of dental check-up and reduced value of aesthetic restoration among undergraduate students in the University of Ibadan. The study shows that despite being aware about dental check-uap and having oral health problems this did not increase the practice of dental visit or increase in the value of aesthetic restoration among the University of Ibadan undergraduates
Keywords: Dental Awareness; check-up; aesthetics; dental visit